Penerapan Metode Waterfall Sisfo Buku Kas Digital Pada Bumdes Jaya Usaha - Sabaruddin, Raja; Murni, Sri; Apriyanti, Aan; Era, Era; Surniya, Surniya (LPPM Universitas Bina Sarana Informatika, 2024)
Efficient and transparent financial management is a crucial factor in optimizing the performance of Village-Owned Enterprises (BUMDes), which aim to support rural economic development. BUMDes Jaya Usaha, located in Bhakti Jaya Village, Meliau District, West Kalimantan, faces challenges in accurately and timely recording financial data due to the limitations of conventional methods, which risk errors, delays, and a lack of transparency. To address these issues, this study develops a digital cash book information system using the Waterfall method, which provides a structured approach to meet system requirements. The implementation of this information system is expected to improve the speed, accuracy, and transparency of financial records, thereby supporting BUMDes Jaya Usaha in making more timely and accurate decisions. Additionally, this study is intended to serve as a model for system development for other BUMDes facing similar challenges. Thus, the implementation of this technology is anticipated to contribute to enhancing financial management quality and the welfare of Bhakti Jaya Village residents